IgA pemphigus showing IgA antibodies to desmoglein 1 and 3 - Salama Hegazy; Sana Bouchouicha; Aida Khaled; Lilia Laadher; Maryem Kallel Sellami; Faten Zeglaoui (Mattioli1885, 2016)
Background: IgA pemphigus is a rare autoimmune vesiculo-pustular skin disease. Only approximately 70 cases have been reported to date. We report a case of IgA pemphigus with IgA antibodies to desmoglein 1 (Dsg1) and desmoglein 3 (Dsg3). Case report: We report the case of an 60-year-old man with intraepidermal neutrophilic IgA pemphigus with IgA antibodies to Dsg1 and Dsg3. Histologic examination revealed subcorneal neutrophilic pustules with few acantholytic cells. The disease was not effectively controlled by conventional therapeutic regimens (colchicine, dapsone). Systemic treatment with isotretinoin 25 mg/d and prednisone 20 mg/d achieved only a slight effect after six months. Conclusions: Our case confirmed the recalcitrant nature of IgA pemphigus in response to distinct therapies, indicating that further research focusing on therapeutic approaches for this type of pemphigus is needed. Physicians should keep IgA pemphigus in mind when approaching patients with bullous eruption.